A large barocaloric effect associated with paramagnetic martensitic transformation in Co50Fe2.5V31.5Ga16 quaternary Heusler alloy. (1st March 2020) - Liu, Hongwei; Li, Zhe; Zhang, Yuanlei; Ni, Zhenting; Xu, Kun; Liu, Yongsheng
Abstract: A martensitic transformation (MT) with paramagnetic behavior has been developed in Co50 Fe2.5 V31.5 Ga16 quaternary Heusler alloy near room temperature. Accompanying the transformation, this alloy shows a good two-way shape memory effect, which results in a considerable relative volume change between two phases. Because of this, it has been also found that the MT is strongly sensitive to the applied hydrostatic pressure. By utilizing an indirectly estimated method, the obtained maximum reversible isothermal entropy (Δ ST ) and adiabatic temperature change (Δ Tad ) resulted from hydrostatic pressure induced MT, respectively, achieve ∼31 J/kg K and 6 K under 5 kbar, performing a large barocaloric effect. Graphical abstract: Image, graphical abstract